Schmitt Trigger Using a Self‐Healing Ionic Liquid Gated Transistor. (22nd April 2015) - Bubel, Simon; Menyo, Matthew S.; Mates, Thomas E.; Waite, J. Herbert; Chabinyc, Michael L.
<x xml:space="preserve">Abstract</x> Electrical double layer transistors using ionic liquids as the gate and ZnO as the semiconductor exhibit stable operation in the presence of redox active additives. The characteristics of the device enable single components with the response of a Schmitt trigger.